Spatial distribution of triatomine bugs in a Chagas disease endemic region in Brazil - Silva,Tatiene Rossana Móta (2019)
Abstract INTRODUCTION: Trypanosoma cruzi is the etiological agent of Chagas disease (CD), a zoonotic infection transmitted by triatomine bug vectors to human beings. Although the story of this parasitic infection was born in Brazil and here this has made major step forward information, the same cannot be said about the actual distribution of the triatomine vector in several areas of this country. The aim of this study was to assess the occurrence of triatomine species in an endemic region for CD in Northeastern Brazil. METHODS: A retrospective study was performed using data obtained from 2008 to 2017. All information was provided by the V Gerência Regional de Saúde of the state of Pernambuco. The spatial distribution of triatomine species was analyzed by drawing a map using the Quantum geographic information system. RESULTS: A total of 4,694 triatomine specimens (469.4 ± 221.2 per year) were collected during the period 2008-2017, with 94.5% (4,434/4,694) at the intradomicile and 5.5% (260/4,694) at peridomicile environment. Of all arthropods collected, 92.5% (4,340/4,694) and 7.5% (354/4,694) were adults and nymphs, respectively. The species most frequently detected were Panstrongylus lutzi (30.36%), Triatoma brasiliensis (26.12%), Triatoma pseudomaculata (22.43%), and Panstrongylus megistus (20.54%). CONCLUSIONS: These data contribute to a better understanding of the distribution of T. cruzi infection in the Northeastern region of Brazil. Preventive measures based on vector control should be implemented in the study area in order to reduce the burden this neglected tropical disease.